2014
DOI: 10.14423/smj.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Filters and Their Varying Compliance with the ACCP and the SIR Guidelines

Abstract: Compliance with the ACCP guidelines is poor in this series; however, much of the discrepancy is based on grade 2C evidence. Only grade 1 evidence will reconcile the differences between the two guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…placement. Furthermore, these guidelines are often not rigorously followed, with filter placement indications varying widely between institutions [15][16][17]. Filters were initially intended for use in patients with VTE and either a contraindication to anticoagulation, a complication of anticoagulation, or a failure of anticoagulation, so-called absolute or "classic" indications [1,18].…”
Section: Devicesmentioning
confidence: 99%
“…placement. Furthermore, these guidelines are often not rigorously followed, with filter placement indications varying widely between institutions [15][16][17]. Filters were initially intended for use in patients with VTE and either a contraindication to anticoagulation, a complication of anticoagulation, or a failure of anticoagulation, so-called absolute or "classic" indications [1,18].…”
Section: Devicesmentioning
confidence: 99%
“…Risk stratification for PTE was performed using Caprini classification preoperatively, and mechanical prophylaxis (i.e., intermittent pneumatic compression) was performed according to the indication. Pharmacological prophylaxis (i.e., heparinization) was not selected due to the nature of surgery, in which excessive bleeding was anticipated [13,14].…”
Section: Surgerymentioning
confidence: 99%
“…Two recent publications focused on compliance with the Society of Interventional Radiology (SIR) and American College of Chest Physician (ACCP) guidelines [1•, 2•, 30]. Both were retrospective studies examining the indications for placement of both permanent and retrievable IVCFs [31,32]. As the SIR guidelines encompass more clinical scenarios in which a filter may be appropriate, it was not surprising that both studies found a higher rate of compliance with these guidelines as compared to the ACCP guidelines.…”
Section: Research In Indicationsmentioning
confidence: 99%